E-Module Mata Pelajaran Kewarganegaraan untuk Meningkatkan Hasil Belajar Siswa - Dian Arief Pradana; Sihkabuden; Arafah Husna (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
This development aims to produce class X Citizenship learning e-module products that can be used as an attractive and effective learning medium. Arief S. Sadiman's (2011) model was used in this development. The result of this development is in the form of an e-module for the Citizenship subject in the competency standard